2016
DOI: 10.1002/adfm.201602337
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of High‐Density Sub‐1‐nm Gaps from Au Nanoparticle Monolayers as Reproducible SERS Substrates

Abstract: The fabrication of ultrasmall nanogaps (sub‐1 nm) with high density is of significant interest and importance in physics, chemistry, life science, materials science, surface science, nanotechnology, and environmental engineering. However, it remains a challenge to generate uncovered and clean sub‐1‐nm gaps with high density and uniform reproducibility. Here, a facile and low‐cost approach is demonstrated for the fabrication of high‐density sub‐1‐nm gaps from Au nanoparticle monolayers as reproducible surface‐e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 57 publications
4
116
0
Order By: Relevance
“…In these studies, the size of the gold nanoparticle is small because of the requirement of high surface activity of the Au nanoparticles. Recently, Si et al demonstrated that high‐density sub‐1 nm gaps can be easily fabricated from Au nanoparticle monolayers by taking advantage of the oil–water interfacial self‐assembly of large‐sized Au nanoparticles (30–120 nm) without any assistance from molecular ligands . Larger Au nanoparticles possess a lower surface charge that decreases the repulsive force between the adjacent nanoparticles at the oil–water interface, thus, the obtained large‐area nanoparticle monolayer generates a high density of sub‐1 nm gaps, as shown in Figure b.…”
Section: Fabrication Methods For Sub‐5 Nm Nanogapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the size of the gold nanoparticle is small because of the requirement of high surface activity of the Au nanoparticles. Recently, Si et al demonstrated that high‐density sub‐1 nm gaps can be easily fabricated from Au nanoparticle monolayers by taking advantage of the oil–water interfacial self‐assembly of large‐sized Au nanoparticles (30–120 nm) without any assistance from molecular ligands . Larger Au nanoparticles possess a lower surface charge that decreases the repulsive force between the adjacent nanoparticles at the oil–water interface, thus, the obtained large‐area nanoparticle monolayer generates a high density of sub‐1 nm gaps, as shown in Figure b.…”
Section: Fabrication Methods For Sub‐5 Nm Nanogapsmentioning
confidence: 99%
“…b) TEM image of Au nanoparticle monolayers with an interparticle distance of 0.5 nm for Au nanoparticles self‐assembled at the oil–water interface. Reproduced with permission . Copyright 2016, WILEY‐VCH Verlag GmbH & Co. c) A scheme for stepwise dimer assembly using masked desilanization (top).…”
Section: Fabrication Methods For Sub‐5 Nm Nanogapsmentioning
confidence: 99%
“…[55] For example, Yang et al achieved a 3D hotspot matrix by evaporating a droplet of plasmonic nanoparticles on a hydrophobic substrate (Figure 6a). To generate SERS substrates with a uniform distribution of hot spots, Si et al proposed oil-water interfacial self-assembly of gold nanoparticles on stretchable poly(dimethylsiloxane) substrates (Figure 6b), [56] which created sub 1 nm gaps of higher density and reproducibility as compared to by using evaporation-based synthesis methods. [55b] However, this platform might suffer from relatively poor signal reproducibility due to the random distribution of hot spots.…”
Section: Self-assembled Nanostructuresmentioning
confidence: 99%
“…[64] These structures were created through the facile solvent wetting (Wenzel state) method, which provides attractive capillary forces among nanopillars (Figure 7a,b). [56] Copyright 2016, Wiley-VCH. [65] Although these close-packed nanoparticles or nanopillars (usually at sub 10 nm) dramatically enhance SERS signaling, they are often subjected to poor reproducibility due to uncontrollable aggregation.…”
Section: Ordered Nanostructuresmentioning
confidence: 99%
“…13,14 However, the last requirement of reproducibility remains one of the biggest challenges in the SERS field. There are various research projects that achieved the creation of a reproducible substrate, 15,16 but the achievement of high detection limit and reproducibility of results (desirably using the portable Raman spectrophotometer) remains a problem. More common methods to realize the uniformity of SERS response (i.e.…”
Section: Introductionmentioning
confidence: 99%